Core-in-cage structure regulated properties of ultra-small gold nanoparticles. Issue 6 (13th May 2019) - Goswami, Nirmal; Bright, Richard; Visalakshan, Rahul Madathiparambil; Biswas, Bhabananda; Zilm, Peter; Vasilev, Krasimir
Abstract : The core-in-cage structure of ultra-small AuNPs can be used to define their functions without compromising their size and surface functionalities. Abstract : Understanding the structure–property relationships of novel materials is pivotal for the advances in science and technology. Thiolate ligand protected ultra-small gold nanoparticles (AuNPs; diameter below 3 nm) constitute an emerging class of nanomaterials with molecule-like properties that make them distinct from their larger counterparts. Here we provide new insights into the structure–property relationships of these nanomaterials by developing a series of ultra-small AuNPs, having comparable size and surface functionalities, but with different core-in-cage structures. We identified the density of metallic core and cage containing Au(i )–thiolate motifs, as well as cage rigidity as crucial factors that can significantly modulate the optical and biological properties of these AuNPs. In particular, AuNPs having a longer motif with a more rigid cage structure exhibited stronger luminescence while those containing a high percentage of loosely bound oligomeric Au(i )–thiolate motifs in the cage (semi-rigid structure) had better antibacterial activity. We also studied for the first time the inflammatory response to these NPs and revealed the importance of cage structure. We envisage that the finding reported in this paper can be applied not only to ultra-small AuNPs but also to other nanomaterials to develop new pathways to exciting future applications in electronics, sensing, imaging and medicine.